A Novel PspA Protein Vaccine Intranasal Delivered by Bacterium-Like Particles Provides Broad Protection Against Pneumococcal Pneumonia in Mice. (19th May 2018) - Wang, Dandan; Lu, Jingcai; Yu, Jinfei; Hou, Hongjia; Leenhouts, Kees; Van Roosmalen, Maarten L.; Gu, Tiejun; Jiang, Chunlai; Kong, Wei; Wu, Yongge
ABSTRACT: Background: Streptococcus pneumoniae is a major pathogen accounting for a large number of pneumococcal disease in worldwide. Due to the mucosal immune pathway induces both systemic and mucosal immune responses, the potential strategy to prevent pneumococcal disease may be to develop a mucosal vaccine. Method: In this study, we developed an intranasal pneumococcal protein vaccine based on a bacterium-like particle (BLP) delivery system. PspA is expressed and exposed on the surface of all pneumococcal strains, which confers the potential to induce immune responses to protect against pneumococcal infection. We fused one of the pneumococcal surface proteins (PspA, family2 clade4) with the protein anchor (PA) protein in order to display PspA on the surface of BLPs. Result: The current results showed that intranasal immunization with BLPs/PspA-PA efficiently induced both PspA-specific IgG in the serum and PspA-specific IgA in mucosal washes. And intranasal immunization of BLPs/PspA-PA could provide complete protection in a mouse challenge model with pneumococci of different two clades of both homologous and heterologous PspA families. Discussion and conclusion: Thus, targeted delivery of multiple bacterial antigens via BLPs may prevent pneumococcal disease by inducing both systemic and mucosal immune responses.